2014
DOI: 10.5935/0103-507x.20140022
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis in intensive care unit patients with traumatic brain injury: factors associated with higher mortality

Abstract: Objective Patients with traumatic brain injury are particularly susceptible to sepsis, which may exacerbate the systemic inflammatory response and lead to organ dysfunction. The influence of clinical variables on the mortality of intensive care unit patients with traumatic brain injury and sepsis was investigated.Methods The present investigation was a retrospective study involving 175 patients with traumatic brain injury who were treated in a period of 1 year at a reference hospital for trauma and who had sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
17
1
6
Order By: Relevance
“…As for length of stay, patients with sepsis, severe sepsis and septic shock stayed for 19.5 to 23.6 days in the intensive care unit. These results differ from other national (14) and international (5,7) data that identified lengths of stay varying from 3.2 to 15.4 days.…”
Section: Discussioncontrasting
confidence: 99%
“…As for length of stay, patients with sepsis, severe sepsis and septic shock stayed for 19.5 to 23.6 days in the intensive care unit. These results differ from other national (14) and international (5,7) data that identified lengths of stay varying from 3.2 to 15.4 days.…”
Section: Discussioncontrasting
confidence: 99%
“…The novelty of this study is a first to report that 97.2% of sepsis patients had a SABD with bad outcome, and unused a rapid antibiotic treatment within the initial 0.5 to 3.0 hours after an early suspected infection event plays a vital role in advancement of high morbidity and high risk of death in SABD. In addition, this high prevalence of SABD with bad outcome can also be explained by the following several points: (1) the low prevalence of SAE in the ICU was from a population without stroke or traumatic brain injure [11,12], whereas, our current study is included these septic patients from stroke and trauma [2,13,15]; (2) our SABD patients were generally associated with a SIRS ≥2, which involves the pathogenesis of SABD contributed by Bone [27], i.e., the cytokines lead to blood brain barrier leakage and cell death [28]. A mixed SABD can be considered if accompanied by a primary brain injure; (3) most SABD in our series is presented with MODS, and the previous studies also indicated that sepsis patients with MODS were more likely to exhibit a SAE [12,21,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, some epidemic studies of SAE showed that a low prevalence varies from 17.7% to 53% of patients with sepsis in ICU, which is unfortunately ruled out stroke or traumatic patients [11,12]. Indeed, acute stroke and traumatic brain injury is more likely to have a secondary sepsis [2,[13][14][15]. However, whether the prevalence of sepsis in ICU patients with critically ill, including acute stroke and traumatic brain injury, would present a leading high prevalence of SABD, which is still unknown.…”
mentioning
confidence: 99%
“…3 Other pulmonary complications, such as acute respiratory distress syndrome (ARDS), pulmonary embolism (PE), and sepsis, were reported to be $ 20%, 1 to 4%, and 50%, respectively. [4][5][6][7] Complications arising in patients with a combination of a severe TBI and an acute subdural hematoma (SDH) can be fatal. 8,9 Early intervention, including prevention of secondary injury to the brain by proactive medical management, is the key to manage the outcomes of these patients.…”
Section: Introductionmentioning
confidence: 99%